Syn reprezentujący Ojca w "De Trinitate" św. Hilarego z Poitiers - Grzywaczewski, Józef (Vox Patrum, 2020)
The aim of this article is to present the teaching of Saint Hilary of Poitiers on the equality of the Son and the Father. Hilary explored the spiritual experience of Abraham, Sarah and Hagar; all of them saw an apparition of an angel, who was not an ordinary messenger of God but God himself, and more precisely – the Son. In a very similar way, the saint interpreted Moses’ experience near the burning bush in the desert: there was an angel, there was God of Israel, and there was the Son. God the Father and Creator cannot appear to people in a visible way. The Son could appear to some because of his connection to the material world. In this sense, theophanies in the Old Testament can be considered as Christophanies. According to Hilary and other Church Fathers, the events of the Old Testament anticipated Christ’s Incarnation. Hilary lived and worked in the time of Arian controversies. He accepted the Creed of Nicaea and he believed that the Son is equal to God the Father by having the same divine nature. Of course, he admitted there is a difference between the missions of the Father and the Son. Hilary’s teaching conformed to the early Christian Tradition as regards theological issues. The theology of the latter centuries, even in our times, has been inspired by the patristic theology found in Hilary’s thoughts.